Analisis Pemberian Kredit Pada Kpri “Harapan” Plumpang - Sindi Kurnia Safitri; Wasti Reviandani (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
This study aims to analyze credit lending in order to minimize non-performing loans at KPRI “HARAPAN” Plumpang. The research was conducted using qualitative methods and data collection techniques through interviews and documentation. The results showed that the credit lending procedures at KPRI “HARAPAN” Plumpang are in accordance with SOP which includes the stages of credit application, credit analysis, credit decision, credit disbursement, and credit supervision. The non-performing loan (NPL) level fluctuates annually, which in 2020 was 4.93% (healthy), in 2021 was 5.58% (fairly healthy), and in 2022 was 4.47% (healthy), although the target NPL to be achieved is 2-3%. Factors causing non-performing loans include bad debt and business closure of customers. Credit supervision efforts undertaken include monitoring non- performing debtors, evaluating the causes of non-performing loans, and internal audits by the Internal Audit Unit (SKAI). To minimize non-performing loans, KPRI